UZBEKISTAN AND TURKMENISTAN - CLOSE NEIGHBORS, BLOOD BROTHERS, RELIABLE PARTNERS (Symposium on Life and Environmental Sciences, 2026)
This article provides information on the close neighborliness between Uzbekistan and Turkmenistan, the history and current state of economic, educational, and cultural relations between them through historical sources and literature.
Keywords: Uzbekistan - Turkmenistan relations, strategic partnership, friendship and cooperation, diplomatic relations, cultural and humanitarian relations, common historical values.